SIKAP KEUANGAN RUMAH TANGGA DESA PADA ASPEK PERENCANAAN KEUANGAN - Perminas Pangeran (Jurnal Riset Akuntansi dan Keuangan, 2012)
The purpose of this study is to examine the financial attitudes of the rural households toward personal finance planning practices. The personal financial planning is associated withdemografic, human capital, dan economic capital characteristics. A survey data is obtained from 197 rural households by using set of structured quesionnaire. The results reveal a number of interesting findings. First, the economic capitals influence financial attitudes toward insurance, investment, and estate planning. Second, the human capitals, i.e. educationof respondent is also the important factors in influencing financial attitudes toward investment planning. Meanwhile, the demographic characteristics of respondent don’t influence attitudes toward household financial planning practices.Keywords: household finance, money, insurance, investment, retirement, and estate